Drivers of social responsibility accounting adoption in Vietnam’s coal industry: Empirical evidence from 23 enterprises amid the energy transition - Hoai, Pham Thi Thu; Vu, Nguyen Thanh (Edelweiss Applied Science and Technology, 2026)
Amid accelerating global commitments to the green transition and sustainable corporate governance, coal mining enterprises, one of the most environmentally intensive sectors, face increasing pressure to internalize socio-environmental responsibilities. Social Responsibility Accounting (SRA), defined as an accounting approach that identifies, measures, and reports social and environmental impacts, has become a key mechanism supporting transparency and accountability in such industries. This study examines the determinants influencing SRA adoption in 23 Vietnamese coal mining enterprises using a quantitative research design with 194 respondents. Drawing upon Institutional Theory, Stakeholder Theory, and Contingency Theory, the analysis tests the effects of five determinants: legal framework, environmental cost management, managerial perceptions, business characteristics, and accountants’ qualifications. Multiple regression results reveal that all five determinants significantly predict SRA adoption, with the legal framework exerting the strongest influence. The findings suggest that Vietnam’s evolving regulatory environment and its national green growth agenda are reshaping accounting practices in heavy industries, positioning SRA as both a compliance requirement and a strategic tool. The study contributes sector-specific empirical evidence from a carbon-intensive industry and provides practical insights for policymakers, enterprise managers, and professional bodies regarding the development of legal guidelines, capacity-building programs, and mechanisms to enhance the effectiveness of SRA implementation.